Exergames in people with major neurocognitive disorder: a systematic review. (19th May 2022) - Swinnen, Nathalie; Vandenbulcke, Mathieu; Vancampfort, Davy
Abstract: Purpose: To systematically evaluate the efficacy of exergames in individuals with major neurocognitive disorder. Materials and methods: PubMed, EMBASE and PEDro were systematically searched from inception until October 2019 for randomised and clinical controlled trials. Methodological quality of the trials was assessed with the PEDro rating scale or Risk of Bias in Nonrandomised Studies of Interventions-I (ROBINS-I), when appropriate. Grading of Recommendations Assessments, Development and Evaluation (GRADE) was used to assess the overall quality of the evidence. Results: Eight trials, all of moderate to high methodological quality (i.e., PEDro score of 6 or higher or a Robins-I moderate quality score) were included. The overall quality of evidence was moderate to high according to the GRADE criteria. Improvements in gait, mobility and balance and beneficial effects on activities of daily living performance, cognitive function, fear of falls, quality of life and mood following exergaming were reported. Heterogeneity in outcome measures, intervention characteristics and included participants precluded a meta-analysis. Conclusions: The current literature is of moderate to high quality and demonstrates that exergames have a wide range of physical and mental benefits in people with major neurocognitive disorder. More controlled trials are however needed to confirm the existing evidence before exergames can be recommended in treatment guidelines for people with major neurocognitive disorder. Implications for rehabilitation: Exergames have many physical and mental benefits in people with major neurocognitive disorder Exergaming can enhance gait, mobility and balance in people with major neurocognitive disorder Evidence for beneficial cognitive effects of exergaming is emerging